ANALISIS EMOSI TOKOH UTAMA DALAM NOVAL HELLO KARYA TERE LIYE - Tamara, Tasya; Seli, Sesilia; Wartiningsih, Agus (Universitas Tanjungpura, 2024)
This research aims to describe the influence of positive and negative emotions on the main character